Identification, Molecular Characterization, and Biology of a Novel Quadrivirus Infecting the Plant Fungus Allocryptovalsa sichuanensis - Yuxu Xie; Xianhong Wang; Xiuyuan Sun; Fanxing Ren; Meng Zhang; Chao Xu; Qingzhou Ma; Yuehua Geng; Rui Zang; Yashuang Guo (Viruses)
A novel double-stranded RNA (dsRNA) virus was isolated and described from strain ZZZ210557 of plant endophyte Allocryptovalsa sichuanensis. The dsRNA virus contains four dsRNA segments, dsRNA1 to dsRNA4, with a size range of 3.8 to 5.1 kbp. Each possesses a single large ORF and is encapsulated in isometric particles approximately 42–47 nm in diameter. Notably, the dsRNA3 encoded sequence revealed modest similarities to the amino acid sequences of RdRps predicted from the nucleotide sequences of known and suspected members of the family Quadriviridae. Phylogenetic analysis of the putative RdRp with the corresponding proteins of other quadriviruses revealed that the dsRNA virus is a new member belonging to the family Quadriviridae, tentatively named Allocryptovalsa sichuanensis quadrivirus 1 (AsQV1). All four segments of AsQV1 could be successfully cured through ribavirin treatment, whereas it likely has no apparent impact on the morphologies or virulence of the host fungus. This study is the first report of a quadrivirus isolated from the fungus A. sichuanensis, and our results enhance the diversity of the quadrivirus.